Inappropriate Use of Words ‘Jihadist’ and ‘Islamist’ in Western Media’s Reports on Bombing Attacks - Purwanto, Bambang; Fenton, Adam James (LSPR Institute of Communication & Business, 2022)
A specific term in Islam’s vocabulary, ‘Jihad’, has been increasingly popular among news readers. Considering huge impacts of news reports, people may expect a lot that mass media can also create news stories that spread values of peace, but do not cultivate seeds of hatred on a certain belief, or persons in society. Not only do the editors and journalists pay attention to the speed of writing, editing and publishing many stories but also consider possible social and even political impacts of their stories on the society. The study is expected to give a significant contribution to media industries as the focus of the study is aimed to give enlightening and right explanation on words, phrases or terms that will be used by media industries in the hope their reports will no longer hurt people, especially Muslims, and/or Muslim organizations as the mass media will hopefully understand the meaning of the terms, words, and phrases which will be used in their stories about any terror incidents, and will eventually give positive impacts to certain groups of people and/or organizations.